Structure and biological evaluation of new cyclic and acyclic laxaphycin-A type peptides. Issue 10 (15th May 2019) - Bornancin, Louis; Alonso, Eva; Alvariño, Rebeca; Inguimbert, Nicolas; Bonnard, Isabelle; Botana, Luis M.; Banaigs, Bernard
Graphical abstract: Abstract: Five new laxaphycins were isolated and fully characterised from the bloom forming cyanobacteria Anabaena torulosa sampled from Moorea, French Polynesia: three acyclic laxaphycin A-type peptides, acyclolaxaphycin A (1 ), [des-Gly 11 ]acyclolaxaphycin A (2 ) and [des-(Leu 10 -Gly 11 )]acyclolaxaphycin A (3 ), as well as two cyclic ones, [l -Val 8 ]laxaphycin A (4 ) and [d -Val 9 ]laxaphycin A (5 ). The absolute configuration of the amino acids, established using advanced Marfey's analysis for compounds2 –5, highlights a conserved stereochemistry at the Cα carbons of the peptide ring that is characteristic of this family. To the best of our knowledge, this is the first report of acyclic analogues within the laxaphycin A-type peptides. Whether these linear laxaphycins with the aliphatic β-amino acid on the N -terminal are biosynthetic precursors or compounds obtained after enzymatic hydrolysis of the macrocycle is discussed. Biological evaluation of the new compounds together with the already known laxaphycin A shows that [l -Val 8 ]laxaphycin A, [d -Val 9 ]laxaphycin A and [des-Gly 11 ]acyclolaxaphycin induce cellular toxicity whereas laxaphycin A and des-[(Leu 10 -Gly 11 )]acyclolaxaphycin A do not affect the cellular viability. An analysis of cellular death shows that the active peptides do not induce apoptosis or necrosis but instead, involve the autophagy pathway.